Assessing the population’s correct knowledge of malaria in Malaysia: a vital component for malaria elimination certification - Faizul Akmal Abdul Rahim; Mohd Farihan Md Yatim; Mohd Hatta Abdul Mutalip; Mohd Amierul Fikri Mahmud (Malaria Journal, 2023)
Abstract Background Malaria remains a public health problem in Malaysia despite a decline in the number of cases in recent years. Public knowledge of malaria is essential to achieving and maintaining malaria elimination. Therefore, this survey assessed the prevalence of people who had ever heard of malaria, had correct knowledge of malaria transmission, symptoms, risk activities, and prevention measures in the Malaysian population, and identified the associated factors involved. Methods The data were obtained from the National Health and Morbidity Survey (NHMS) which was conducted from September to October 2020. A cross-sectional survey with five structured questionnaires using the method of computer-assisted telephone interviews (CATI) was used to collect data. The socio-demographic characteristics such as age, gender, ethnicity, nationality, marital status, educational level, and occupation were recorded. Data were analysed using STATA SE Version 16. Associations between variables were tested using chi-square and logistic regression, with the level of statistical significance set at p < 0.05. Results Out of 3085 respondents who participated in this survey, 2491 had ever heard of malaria with a prevalence of 76.1% (95% CI 70.5, 80.9). The prevalence of correct knowledge of malaria transmission was 53.9% (95% CI 50.2, 57.7), symptoms 24.1% (95% CI 21.2, 27.2), risk activities 34.0% (95% CI 29.3, 39.1) and prevention measures 59.7% (95% CI 55.5, 63.7). Multivariate analysis showed that age, ethnicity, and educational level were significantly associated with correct malaria transmission and risk activities. In addition, age and educational level were significantly associated with correct malaria symptoms. Subsequently, only the variable ethnicity showed a significant association with the correct malaria prevention measures. Conclusion In general, the prevalence of ever heard of malaria was considered high since the survey was performed based on a non-specific malaria population. However, the prevalence of correct knowledge of malaria symptoms and risk activities were considered low. It is concluded that educational level is one of the major factors associated with correct malaria knowledge, along with age and ethnicity. Therefore, based on these findings, targeted intervention and innovation should be planned by malaria programme managers to sustain malaria elimination in Malaysia.